Compositional range and crystal fractionation of basaltic pillows from Ármannsfell, SW-Iceland - Sigríður Inga Svavarsdóttir 1990- (2014)
Olivine tholeiite pillows from Armannsfell, SW-Iceland, were collected in order to reveal chemical and mineralogical fractionation among the different lithofacies of the pillows; the rim, crust and core. Whole rock composition of pillow units range from 11 to 20 Wt % ol in the norm. Detailed EDS analysis of rim-glass and residual glass shows dominating ol-tholeitie composition ranging from 15 % ol in the norm towards subordinate qz-tholeiite with 2.7 % qz in the norm. Minor intermediate and silicic residual glass is found in the pillow cores, ranging up to 25 % qz in the norm. Detailed SEM and EDS analyses of the pillow units show that olivine phenocrysts (85 % Fo) and plagioclase (88 % An) microphenocryst in the pillow rim existed in a cotectic relation prior to eruption of the pillow basalt. The crystallization of ol (85-72 % Fo) and plag (88-64 % An) continues into the pillow crust where clinopyroxene augite enters the assemblage. Clinopyroxene with Ti-augite (5 Wt % TiO2) composition is formed until titanomagnetite enters the mineral assemblage. Towards the end of crystallization, common augite (2 Wt % TiO2) crystallizes with olivine, plagioclase and magnetite. Magnetite composition ranges from 70-59 % Usp in the absence of ilmenite. Crystal fractionation of the melt and mechanical fractionation of ol phenochrysts along the pillows obscures the composition of the primary magma. This demands whole rock analyses of several pillow-units in order to find a representative sample of pillow basalt. Sýnum af ólivín-þóleiíti í bólstrabergi úr Ármannsfelli var safnað til að kanna efnafræðilegan og steindafræðilegan breytileika í mismunandi berggerðum bólstranna; glerrima, skorpu og kjarna. Bergsamsetning bólstraeininganna er breytileg frá 11 í 20 % ol í normi. Ítarleg EDS greining á bólstragleri og afgangsgleri sýnir ríkjandi ol-þóleiít samsetningu þróast frá 15 % ol í normi í átt að smáræði af qz-þóleiíti með 2.7 % qz í normi. Í kjarna bólstranna finnst smáræði af ísúru og súru gleri allt að 25 % qz í normi. ...